Pengaruh Pendidikan Kesehatan Terhadap Pengetahuan Ibu-Ibu Tentang KB IUD Di Dusun Plosorejo Desa Jagir Kecamatan Sine Kabupaten Ngawi - Hidayatulloh, Ridho; , Dr. Faizah Betty Rahayuningsih A., S.Kep, M.Kes (2017)
Family planning acceptors in jagir village, the number of acceptors IUD only 143 people or 19,3 % . there were No additional acceptors iud in the last year . One factor that can affect the low IUD acceptors was a lack of knowledge of IUD . Education and health was one way to increase mother's knowledge of IUD contraseption. The objective was to know an effect of education health of mother's knowledge of contraceptives IUD in plosorejo. Design of study use pre experimental and pre test and post test one group design. The number of samples was 40 mothers and taking sample use purposive sampling technique. Intrumen study of education health with the questionnaire knowledge of IUD, media use leflet and banner. An analysis of data using the one sample test. The results show when pre test there were 24 respondents with poor knowledge, 14 respondents with fair knowledge and, and 2 respondents with high knowledge. In post test, one respondens with poor knowledge, 16 respondents with fair knowledge and , and 23 respondents with high knowledge.The results of the analysis statistic dipeeroleh value p = 0,001 .Conclusion : education health impact on knowledge mothers about IUD family planning in dusun plosorejo, jagir village kecamatan sine sub district ngawi in april 2017. Increased knowledge by respondents after giving education health by 38,21 %.